A contingency-based decision support instrument for selecting lean production tools and techniques - Yahya, Mohd Shahir (2021)
This study is about the development of decision support instrument for selecting lean tools and techniques based on the contingency factors to help Malaysian organizations to select the right lean tools and techniques based on their context. Most of the prior studies were found focusing on the selection lean tools but did not assess the critical contingency factors that may influence the selection of lean tools and techniques. Adding to that, there were no similar studies on the selection of lean tools and techniques within the Malaysian context. The right tools and techniques to be used may vary depending on several factors, therefore to keep away from unnecessary waste and dissatisfaction, it would be better for organization to choose the right lean tools and techniques that will fit with organization’s situation and give benefits to the organization. A mixed-methods study exclusively focused on the development, evaluation, and refinement of a decision support instrument or specifically known as “Decision Aid for Lean Tools and Techniques Selection” (DEALS) was used. The developed decision support instrument, which incorporates 10 most widely used lean tools and techniques was emphasises the use of holistic processes which start from diagnose their current state of waste until the guidance of selecting the appropriate lean tools and techniques. Additionally, contingency factors were employed to include multifaceted viewpoints and contexts in the development of DEALS, such as the adeptness to acquire the commitment and support from the top management and the advantages of implementing lean tools and techniques. The developed decision support instrument includes two selection methods, namely (1) simple additive weighting (SAW) for basic selection and (2) analytic hierarchy process (AHP) for more advanced selection. Based on the evaluation results, all respondents (100%) agreed on the usability, accuracy, and novelty of DEALS as well as the relevance and validity of the selection and the clarity of the purpose of DEALS. The final results of validation testing also shows less than 5% errors when comparing final results of DEALS with two established software which are Expert Choice 11 software and Super Decision Software. By having this DEALS, it expected significantly benefit to managers, practitioners, consultants, researchers, and academicians as a guidance instrument in the selection of lean tools and techniques and generally to organization to have knowledge workers.